Analisis Manajemen Risiko Pada Usaha Toko Apotek Di Kabupaten Tegal - Prayogo, Yanuar Rizqi; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The number of pharmacies in Indonesia, including in Tegal Regency, has increased rapidly in recent years, along with the deregulation of pharmacy establishment, rising demand for medicines, and the growing number of pharmaceutical personnel. Data were obtained through questionnaires filled out by pharmacy owners and managers directly involved in daily operations, so the information collected reflects the real conditions in the field. The approach used is quantitative descriptive, focusing on three main stages of risk management. These findings underscore the importance of implementing more structured risk management so that pharmacies can maintain service quality and minimize potential losses amid the continuously evolving healthcare industry.